E-HEALTH SCHOOL REPORT: PENCEGAHAN PERILAKU BERISIKO PADA REMAJA MELALUI KONSEP TRIPLE HELIX - Ramadhani, Andi Tis’a; Ali, Muhammad Fauzan; Fajrin, Marwah Nur; Ismail, Fardhila Khairunnisa; Akbar, Richal; Yusnitasari, Andi Selvi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Health at school age is an important aspect because of the link between health and academic function. Teenagers carry out various risky behaviors, such as smoking, lack of physical activity, lack of consumption of fruit and vegetables. Therefore, the E-Health School Report program: Triple Helix Concept Approach to Prevent Health Risk Behavior among Students at SMAN 7 Takalar. This program consists of 4 main activities, namely 1) Selection and training of youth cadres; 2) Establishment of a student health post; 3) Adolescent risk behavior screening and health education; 4) Recording and reporting student health in the E-Health School Report. Apart from involving students, this program also involves parents and teachers to monitor students’ health. The results of the activities that have been carried out are, as many as 10 adolescent cadres who have been trained to carry out risk behavior screening of adolescents have been able to measure body mass index, provide health education, record and report health on the E-Health School Report, and have available student health posts. as a forum for cadres to carry out health screening and education. It is hoped that schools will routinely carry out this activity to monitor students’ health problems